Correlation Between Thalamus-Related Functional Connectivity and Serum BDNF Levels During the Periovulatory Phase of Primary Dysmenorrhea - Han, Fang; Liu, Hongjuan; Wang, Ke; Yang, Jing; Yang, Ling; Liu, Jixin; Zhang, Ming; Dun, Wanghuan (Frontiers in Human Neuroscience, 2019)
The thalamus is a key region for the transmission of nociceptive information in the central modulation of pain and has been studied in the setting of numerous chronic pain conditions. Brain-derived neurotrophic factor (BDNF) is considered an important modulator for mediating nociceptive pathways in chronic pain. The present study aimed to investigate whether there was thalamus-related abnormal functional connectivity (FC) or relevant serum BDNF level alterations during periovulation in long-term primary dysmenorrhea (PDM), a kind of chronic visceral pain. Functional connectivity analyses were performed using 3-dimensional T1-weighted and resting-state functional magnetic resonance imaging (fMRI) in 36 patients in the periovulatory phase and 29 age-, education-, and gender-matched healthy controls. Serum BDNF levels were evaluated by enzyme-linked immunosorbent assay and a significantly higher BDNF level was detected in PDM patients. Regions of abnormal thalamus-related FC of pain perception included the primary sensory cortex (SI), bilateral dorsolateral prefrontal cortex, hippocampus and periaqueductal gray (PAG) in PDM patients. Further analysis revealed significant positive correlations between serum BDNF levels and thalamus-related FC in regions associated with pain perception including the orbitofrontal cortex, SI and SII areas, and inferior parietal area. Our results suggest greater dysfunction in thalamus-related FC in PDM (even in the absence of ongoing menstrual pain) that is likely correlated with underlying modulative effects of abnormal serum BDNF levels. Such alterations partly account for hyperalgesia in women with PDM. In addition, our study advances methods of cerebral functional investigation.